Function minimization in DNA sequence design based on continuous particle swarm optimization - Khalid, Noor Khafifah (ICIC Express Letters Office, 2009)
In DNA based computation and DNA nanotechnology, the design of good DNA sequences has turned out to be an essential problem and one of the most practical and important research topics. Basically, the DNA sequence design problem is a multi-objective problem, and it can be evaluated using four objective functions, namely, Hmeasurei similarity, continuity, and hairpin. In this paper, particle swarm optimization (PSO) is proposed to minimize those objective functions, individually, subjected to two constraints: melting temperature, Tm, and GCcontent. A model is presented in order to minimize the objective functions using PSO. An implementation of the optimization process is presented using 20 particles. The results obtained verified that PSO can be used to minimize each objective individually.